Metabolic Syndrome, Obesity, and Gastrointestinal Cancer - Shintaro Fujihara; Hirohito Mori; Hideki Kobara; Noriko Nishiyama; Mitsuyoshi Kobayashi; Makoto Oryu; Tsutomu Masaki (Gastroenterology Research and Practice)
Metabolic syndrome is a cluster of metabolic abnormalities and is defined as the presence of three or more of the following factors: increased waist circumference, elevated triglycerides, low high-density lipoprotein cholesterol, high blood pressure, and high fasting glucose. Obesity, which is accompanied by metabolic dysregulation often manifested in the metabolic syndrome, is an established risk factor for many cancers. Adipose tissue, particularly visceral fat, is an important metabolic tissue as it secretes systemic factors that alter the immunologic, metabolic, and endocrine milieu and also promotes insulin resistance. Within the growth-promoting, proinflammatory environment of the obese state, cross-talk between macrophages, adipocytes, and epithelial cells occurs via obesity-associated hormones, adipocytokines, and other mediators that may enhance cancer risk and progression. This paper synthesizes the evidence on key molecular mechanisms underlying the obesity-cancer link.